Sie sind auf Seite 1von 3

LIMIT 6

C.
2 13
𝑥 −4 13
1. lim = … D. −
𝑥→2 𝑥3 + 1 6
E. −3
A. 0 𝑥 2 + 3𝑥 − 18
4. lim = …
B. 1 𝑥→3 𝑥 2 − 3𝑥
C. 2 A. 0
D. 3 B. 1
E. ~ C. 2
2𝑥 2 − 𝑥 − 1 D. 3
2. lim = … E. 6
𝑥→1 3𝑥 2 − 𝑥 − 2
A.
3 𝑥 3 − 3𝑥 2 − 3𝑥 − 4
5 5. lim = …
2 𝑥→4 𝑥 2 − 4𝑥
B. A. 0
3
1 21
C. B.
2 4
33
D. 0 C.
4
E. ~ 37
3𝑥 2 − 5𝑥 − 12 D.
4
3. lim = … E. ~
𝑥→3 𝑥2 − 9
A. 3
13
B.
6
𝑥−9 𝑥2 − 1
6. lim = … 11. lim = …
𝑥→9 √𝑥 − 3 𝑥→−1 √8 − 𝑥 − 3
A. 6 A. 0
B. 4 B. 6
C. 3 C. 8
D. 1 D. 10
E. 0 E. 12
𝑥−2 9 − 𝑥2
7. lim = … 12. lim = …
𝑥→2 √𝑥 + 7 − 3 𝑥→3 4 − √𝑥 2 + 7
A. -2 A. 8
B. -1 B. 4
C. 0 C. 2
D. 6 D. 1
E. 12 E. 0
1−𝑥 𝑥2 − 9
8. lim = … 13. lim = …
𝑥→1 2 − √𝑥 + 3
𝑥→3 √𝑥 2 + 16 − 5
A. 8 A. 10
B. 4 B. 8
C. 0 C. 5
D. -4 D. -3
E. -8 E. -5
2 − √𝑥 + 1 2 − √𝑥 + 2
9. lim = … 14. lim 2 = …
𝑥→3 𝑥−3 𝑥→2 𝑥 − 5𝑥 + 6
1
A. − A. −
1
4
1 4
B. − B. −
1
2
10
C. 1 1
D. 2 C.
4
1
E. 4 D.
20
4−𝑥 1
10. lim = … E.
10
𝑥→4 2 − √𝑥
A. 0 √(𝑥 + 2) − √(3𝑥 − 2)
15. lim = …
B. 1 𝑥→2 𝑥−2
1
C. 2 A. −
2
D. 4 B. 0
E. 6 1
C.
2
D. 1
E. 2
4𝑥 E. 4
16. lim = … 𝑥−8
𝑥→0 √1 − 2𝑥 − √1 + 2𝑥 17. lim 3 = …
A. -2 𝑥→8 √𝑥 − 2
B. 0 A. 8
C. 1 B. 12
D. 2 C. 16
D. 20
E. 24 (4𝑥 − 1)3
3 22. lim = …
√𝑥 − 3 𝑥→∞ 2𝑥 3 − 1
18. lim = … A. 0
𝑥→27 𝑥 − 27
A. ~ B. 2
B. 3 C. 8
C. 1 D. 16
1 E. 32
D.
27 2𝑥 2 + 3𝑥
E. 0 23. lim = …
3𝑥 2 − 2𝑥 − 8 𝑥→∞ √𝑥 2 − 𝑥
19. lim = … A. 0
𝑥→∞ 9𝑥 2 − 16 1
A. 3 B.
2
1
B. C. 1
3
C. 0 D. 2
D. -3 E. ~
E. ~ 24. lim 𝑥 − √𝑥 2 − 4𝑥 + 2 = …
𝑥→∞
7𝑥 2 − 7𝑥 − 10 A. 0
20. lim = …
𝑥→∞ 2 − 𝑥2 B. 1
A. 3 C. 2
B. 0 D. 4
C. -7 E. 8
D. ~
25. lim (2𝑥 − 1) − √4𝑥 2 − 5𝑥 + 2 = …
E. Tak tentu 𝑥→∞
1
𝑥2 − 4 A. −
21. lim 3 = … 2
𝑥→∞ 𝑥 + 1 1
B. −
A. 0 4
1
B. 1 C.
4
1 1
C. D.
9 2
2
D. E. 1
3
E.~

26. lim 9𝑥 2 − 6𝑥 − 1 − (3𝑥 + 1) = … sin 3𝑥
𝑥→∞ 31. lim = …
𝑥→0 8𝑥
A. -4 A. 1
B. -3 B. 0
C. -2 3
C.
D. 0 8
8
E. 1 D.
3
27. lim √𝑥 2 − 2𝑥 + 5 − √𝑥 2 + 2𝑥 + 11 = … E. ~
𝑥→∞
sin 2𝑥
A.-4 32. lim = …
B.-2 𝑥→0 sin 4𝑥
1
C.0 A.
2
D.2 B. 1
E.~ C. 2
28. lim 4𝑥 2 + 3𝑥 + 4 − √4𝑥 2 − 5𝑥 + 4 = …
√ D. 0
𝑥→∞ E. ~
A.4 sin 2𝑥
B.2 33. lim = …
𝑥→0 tan 3𝑥
C.0 A. 1
D.1 2
E.~ B.
3
√4 + 𝑥 2 − √2 + 𝑥 2 C. 0
29. lim = … D. -1
𝑥→∞ 3𝑥 E. ~
A. 0
1 3𝑥 tan 2𝑥
B. 34. lim = …
3 𝑥→0 5𝑥 sin 4𝑥
2 3
C. A.
3 10
D. 2 3
B.
E. ~ 5
1
√5 − 4𝑥 + 3𝑥 2 − √4 − 3𝑥 + 3𝑥 2 C.
2
30. lim = … 2
𝑥→∞ 2𝑥 D.
5
A. 0 3
1 E.
B. √3 4
3 sin 2𝑥
C. √3 35. lim = …
𝑥→0 3 − √2𝑥 + 9
D. 2√3 A. -6
E. ~ B. -3
C. 0
D. 6 B. 2
E. 12 C. -1
(4𝑥 − 10) sin(𝑥 − 5) D. -2
36. lim = … E. -4
𝑥→5 𝑥 2 − 25
A. -3 2𝑥 tan 3𝑥
45. lim = …
B. -1 𝑥→0 1 − cos 2 𝑥
C. 1 A. 0
D. 2 B. 2
E. 4 C. 3
(𝑥 2 − 4) tan 3𝑥 D. 6
37. lim 3 = … E. 12
𝑥→0 𝑥 + 5𝑥 2 + 6𝑥
A. -4 1 − cos 2𝑥
46. lim = …
B. -2 𝑥→0 2𝑥 sin 2𝑥
1
C. 0 A.
8
D. 1 1
B.
E. 3 6
1
C.
4
2𝑥 2 − 3𝑥 − 9 D.
1
38. lim = … 2
𝑥→3 𝑥 sin(2𝑥 − 6)
2
E. 1
A. − 1 − cos(𝑥 + 2)
3
B. −1 47. lim = …
𝑥→0 𝑥 2 + 4𝑥 + 4
1 A. 1
C. −
2 1
D. 1 B.
2
3 1
E. C.
2 4
1
sin2 3𝑥 D. −
39. lim = … 4
𝑥→0 2𝑥 tan 3𝑥 1
3 E. −
A. 2
2
3
(𝑥 2 − 4) ∙ tan(𝑥 + 2)
B. 48. lim = …
6 𝑥→−2 sin2 (𝑥 + 2)
9
C. A. –4
2
D. 1 B. –3
E. ~ C. 0
D. 4
cos 2𝑥 − 1 E. ∞
40. lim = … 𝑥 ∙ tan(2𝑥 − 6)
𝑥→0 𝑥2 49. lim = …
A. -2 𝑥→3 sin(𝑥 − 3)
B. 0 A. 0
1
C. 1 B.
2
D. 2 C. 2
E. Tak tentu D. 3
8𝑥 2 E. 6
41. lim = …
𝑥→0 1 − cos 2𝑥 1 − cos 2 2𝑥
A. -4 50. lim = …
𝑥→0 𝑥 sin 2𝑥
B. -2 A. 4
C. 2 B. 2
D. 4 C. 0
E. 8 D. –2
1 − cos 𝑥 E. –4
42. lim = …
𝑥→0 𝑥 sin 2𝑥
A. 0
1
B.
8
1
C.
4
1
D.
2
E. 1
𝑥 tan 𝑥
43. lim = …
𝑥→0 1 − cos 2𝑥
A. -1
1
B. −
2
C. 0
1
D.
2
E. 2
cos 4𝑥 − 1
44. lim = …
𝑥→0 𝑥 tan 2𝑥
A. 4